Superstructure damages due to the joint effects of differential ground settlement and machinery vibration: a case study - Xin Liao; Zhiliang Chen; Weiyong Dai; Liming Qu; Zhuowu Xie; Qiang Tang (Geomatics, Natural Hazards & Risk)
Prioritizing safety management and operational maintenance within hydropower stations proves imperative for both economic development and environmental protection. This study analyzed the joint effects of differential ground settlement and machinery vibration on the superstructure damages through a real case that happened in a hydropower station located in Sichuan province (China). A combination of on-site investigations, field experiments, and numerical simulations are employed to recognize the abnormal vibrations, replicate soil vibration patterns, and comprehend the underlying causes of settlement. Guided by the identified causes, a judicious selection of the optimal vibration reduction solution transpired, subsequently validated through numerical simulations. The outcomes underscore that during operational phases uneven settlement ensues owing to the presence of a feeble foundation. This differential settlement in turn exacerbates foundation settlement by amplifying vibrations in the generator units. The geological conditions of the hydropower station remain in a perpetual state of evolution influenced by surface geological processes. Consequently, a protracted and scientific assessment of hydropower station geological conditions holds enduring significance for both the realms of engineering construction and operational maintenance.